2016
DOI: 10.20452/pamw.3695
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: the dynamic epidemiology of cardiovascular diseases

Abstract: 839the results of data regarding the characteristics and outcomes of about half million CV patients between 2006 and 2014 in Poland, is both interesting and important. The main findings of the latter study include the following temporal trends: 1) no significant change in the annual number of hospital admissions for CVD; 2) a shorter length of in-hospital stay for CVD admissions; 3) a decrease in the overall readmission rate; and 4) stable, with some tendency towards a decrease, in-hospital and 12-month adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Throughout the past decades, a significant decline in the rate of ST-segment elevation acute myocardial infarction (STEMI) hospitalizations but not of non-STEMI (NSTEMI) was observed. 1 5 Improvements in outcomes were also reported for patients with STEMI in particular. 1 4,6 9 It has been suggested that these changes are explained, at least partially, by temporal changes in the prevalence of cardiovascular risk factors (CVRFs) in AMI.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Throughout the past decades, a significant decline in the rate of ST-segment elevation acute myocardial infarction (STEMI) hospitalizations but not of non-STEMI (NSTEMI) was observed. 1 5 Improvements in outcomes were also reported for patients with STEMI in particular. 1 4,6 9 It has been suggested that these changes are explained, at least partially, by temporal changes in the prevalence of cardiovascular risk factors (CVRFs) in AMI.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3][4][6][7][8][9] It has been suggested that these changes are explained, at least partially, by temporal changes in the prevalence of cardiovascular risk factors (CVRFs) in AMI. 3,5 The burden of CVRFs was demonstrated in an analysis of over 120 000 patients with acute coronary syndrome (ACS) enrolled in 14 international randomized clinical trials that showed at least 1 of 4 conventional risk factors (smoking, diabetes mellitus [DM], dyslipidemia, and hypertension) was present in >80% of patients. 5,10 The Framingham risk score (FRS) comprises the following CVRFs: age, blood pressure, total cholesterol, high-density lipoprotein cholesterol (HDL-C), smoking, and DM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations